Cultural Transmission through the TikTok Application, Study on Pop Minang as a Local Language Song - Ladyanna, Sonezza (Vivid: Journal of Language and Literature, 2024)
This article aims to explain how cultural transmission occurs in the flowof globalization through the TikTok application. The culture is referred toas Minangkabau culture. People identifying themselves as Minangkabaupopulate the contemporary Indonesian province of West Sumatra and arefound in immigrant communities throughout the archipelago, Malaysia,Australia, and further afield, and they are known for their Islamic piety,matrilineal kinship system, astute trading abilities, proclivity to migrate,democratic practices, and spicy food (Fraser J. A., 2015, p. 3). Thisresearch focuses on Pop Minang, a genre of regional language songs usedin content on the TikTok application. Songs that are broadcast on the socialmedia application TikTok also become transmitters of traditional culturefor the younger generation in that culture and even the cultures of otherpeoples. The results of this study are in contrast to previous studies, whichclaim that TikTok and globalization have a negative impact on the youngergeneration (Kurniawan, 2018; Sairin, 2004) and support the opinion thatglobalization is a process of glocalization or the interaction and mergerbetween local cultures and global processes (Turner, 2015, p. 5).